Cutaneous Allodynia of the Withers in Cattle: An Experimental In Vivo Neuroanatomical Preliminary Investigation of the Dichotomizing Sensory Neurons Projecting into the Reticulum and Skin of the Withers—A Case Study on Two Calves - Roberto Chiocchetti; Luciano Pisoni; Monika Joechler; Adele Cancellieri; Fiorella Giancola; Giorgia Galiazzo; Giulia Salamanca; Rodrigo Zamith Cunha; Arcangelo Gentile (Animals)
The presence of dichotomizing neurons in the dorsal root ganglia (DRG) of cattle, innervating both the reticulum and the withers, may indicate a pre-spinal convergence of visceral and cutaneous sensory information, i.e., that the DRG primary sensory neurons may elaborate the sensory information coming from two different anatomical areas before reaching the secondary sensory neurons within the spinal cord. This anatomical feature could be the underlying basis for the cutaneous allodynia observed in traumatic reticuloperitonitis, also known as the “Kalchschmidt pain test”. The aim of the study was to identify the DRG primary sensory neurons innervating the reticulum and the withers by using two different retrograde fluorescent tracers, Fast Blue (FB, affinity for cytoplasm) and Diamidino Yellow (DY, affinity for nucleus). In two anesthetized calves, FB and DY were injected into the reticulum and skin of the withers, respectively. At the end of the experimental period, the calves were deeply anesthetized and then euthanatized. The thoracic (T1–T8) DRG were collected and processed to obtain cryosections which were examined on a fluorescent microscope. A large number of neurons localized, especially in the T7 DRG, presented nuclei labeled with DY. On the contrary, only a few neurons localized exclusively in T6 and T7 DRG presented the cytoplasm labeled with FB. No neurons displayed FB and DY simultaneously within the cytoplasm and nucleus, respectively. The absence of double-labeled DRG neurons suggests that the convergence of visceral and somatic sensory inputs underlying the Kalchschmidt pain response likely does not occur at the level of individual DRG neurons. Rather, it may involve higher-order integrative centers, possibly including vagal pathways and brainstem nuclei which integrate the afferent information to coordinate respiratory movements of the diaphragm, intercostal muscles, and larynx. Although limited by the sample size, this case study provides a neuroanatomical basis for further investigation into central mechanisms of referred visceral pain in cattle.